2021
DOI: 10.1111/ina.12844
|View full text |Cite
|
Sign up to set email alerts
|

Solid cooking fuel use and cognitive decline among older Mexican adults

Abstract: Studies of air pollution and cognition often rely on measures from outdoor environments. Many individuals in low‐ and middle‐income countries are exposed to indoor air pollution from combustion of solid cooking fuels. Little is known about how solid cooking fuel use affects cognitive decline over time. This study uses data from the 2012, 2015, and 2018 Mexican Health and Aging Study (n = 14 245, age 50+) to assess how use of wood or coal for cooking fuel affects cognition of older adults relative to use of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Biomass fuel cooking has major health implications throughout life course (e.g., low-birthweight, respiratory infections, chronic obstructive pulmonary disease (COPD)), cognitive impairment, etc.) [2][3][4][5] and also exerts adverse environmental (e.g., deforestation, erosion, greenhouse gas emissions etc.) [6,7] and socioeconomic impacts (e.g., gender inequalities, healthcare costs, opportunity costs etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Biomass fuel cooking has major health implications throughout life course (e.g., low-birthweight, respiratory infections, chronic obstructive pulmonary disease (COPD)), cognitive impairment, etc.) [2][3][4][5] and also exerts adverse environmental (e.g., deforestation, erosion, greenhouse gas emissions etc.) [6,7] and socioeconomic impacts (e.g., gender inequalities, healthcare costs, opportunity costs etc.)…”
Section: Introductionmentioning
confidence: 99%
“…These factors are also largely influenced by differential exposure (e.g., by nativity status and country of origin) to myriad social, economic, political, behavioral, and environmental determinants of brain health. Furthermore, the differences we continue to observe among nativity and country of origin Latino subgroups, and in comparison to U.S.-born non-Latino Whites, may reflect differential environmental exposures given the growing evidence that urban air pollution and indoor air pollution (i.e., combustion of solid cooking fuels in low- and middle-income countries) affect cognitive health ( Ailshire & Clarke, 2015 ; Ailshire & Crimmins, 2014 ; Kulick et al, 2020 ; Saenz, 2021 ; Saenz et al, 2018 , 2021 ). Future research should aim to further investigate differences in such exposure across groups by, for example, matching respondents on urbanicity to account for factors associated with cognition not captured in this study.…”
Section: Discussionmentioning
confidence: 91%
“…The association between solid fuel use and cognitive impairment has been frequently determined in China, while the evidence from other areas is limited ( 30 , 60 , 78 ). A study from Mexico suggested that solid cooking fuels may represent a risk factor for cognitive decline ( 79 ). Additionally, the association between solid fuel and depressive symptoms for ten years depended on the WHO Study on Global AGEing and Adult Health (SAGE) ( 80 ).…”
Section: Discussionmentioning
confidence: 99%